Munculnya Calon Tunggal di Pilkada Batang Hari Tahun 2024: Analisis Pada Perspektif Seek Efficiency dalam Pembentukan Koalisi Partai Politik - fajri, syabina laura; Subekti, Dimas; Pratiwi, Cholillah Suci (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The emergence of a single candidate in the 2024 Batang hari Regional Election represents an interesting illustration of political party strategies in responding to local democratic dynamics. This study aims to analyze the formation of a grand political coalition through the seek efficiency perspective, referring to the concept of political efficiency proposed by(Pamungkas & Parlindungan, 2011). This research employs a qualitative descriptive approach, with data collected through interviews, documentation, and online media analysis. The findings reveal that the establishment of a grand coalition supporting the incumbent pair, Fadhil Arief and Bakhtiar, was primarily motivated by political efficiency considerations in utilizing resources such as time, energy, and cost. Cross-party cooperation was viewed as a strategic measure to enhance campaign effectiveness and strengthen electoral support. For core parties such as PPP and NasDem, this efficiency became more evident once the coalition operated with proper coordination and proportional role distribution. Overall, the study illustrates that coalition formation in Batang Hari reflects a form of rational political behavior oriented toward effectiveness and efficiency, as well as an effort to strengthen local democratic stability through productive political collaboration